Pemberdayaan Petani Lokal dengan Pelatihan Manajemen Usaha Agribisnis di Desa Bandar Jaya - Citra Rianzani; Subandi; Astri Shabrina; Akmal Attamimi (Wisanggeni: Jurnal Pengabdian Masyarakat, 2021)
Abstract: The agribusiness business management training in Bandar Jaya Village is a form of community service that aims to empower local farmers to have managerial skills in managing agribusiness activities effectively and sustainably. Through a participatory approach, this activity provides an understanding of business planning, financial recording, cost and income analysis, and product marketing strategies. The results showed a significant improvement in participants' ability to develop business plans and understand the importance of cost efficiency. This activity is expected to be the foundation of farming transformation towards productive and market-oriented agribusiness patterns. Keywords: empowerment, agribusiness management, training, local farmers, farm business